Efektifitas Kombinasi Akupresure dan Minuman Jahe (Zingiber Officinale) terhadap Emesis Gravidarum di Desa Bandar Setia Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Nikmah Jalilah Ritonga; Fahma Shufyani; Elsaria Br. Sembiring (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Emesis gravidarum is a common complaint made in young pregnancies. Preganancy causes hormonal changes in women due to an increase in estrogen, progesteron, and the realease of the placental chorionic gonodothropine hormone. Emesis gravidarum usually occurs in the morning, but there are those that arise at any time of the night. Feelings of nausea are caused by increased levels of the hormones estrogen an human chorionic gonadothropine (hCG) in the serum. The purpose of this study was to determine the effect of giving a combination of acupressure and ginger drinks at Bandar Setia Village 2020. This type of research is quantitative research, using a quasy experiment design study with the design of Three-Groups Pretests-Posttest design control. The study population was pregnant women who experienced emesis gravidarum in Desa Bandar Setia. Sampling using Probability Sampling technique that is Simple Random sampling by determining the inclusion and exclusion criteria of 45 pregnant women who will be divided into three groups, 15 people for the experimental group who were given acupressure only, 15 people for the experimental group who were given ginger drinks only, and 15 experimental groups were given a combination of acupressure and ginger drink.The results of the study using Wilcoxon test obtained p-value = 0.000 <0.05. The conclusion is there is an effect on pregnant women who experience emesis gravidarum after being given a combination of acupressure and ginger drink.